Effects of low-frequency stimulation of the subthalamic nucleus on movement in Parkinson's disease. - Eusebio, A; Chen, C; Lu, C; Lee, S; Tsai, C; Limousin, P; Hariz, M; Brown, P (2008)
Excessive synchronization of basal ganglia neural activity at low frequencies is considered a hallmark of Parkinson's disease (PD). However, few studies have unambiguously linked this activity to movement impairment through direct stimulation of basal ganglia targets at low frequency. Furthermore, these studies have varied in their methodology and findings, so it remains unclear whether stimulation at any or all frequencies < or = 20 Hz impairs movement and if so, whether effects are identical across this broad frequency band. To address these issues, 18 PD patients chronically implanted with deep brain stimulation (DBS) electrodes in both subthalamic nuclei were stimulated bilaterally at 5, 10 and 20 Hz after overnight withdrawal of their medication and the effects of the DBS on a finger tapping task were compared to performance without DBS (0 Hz). Tapping rate decreased at 5 and 20 Hz compared to 0 Hz (by 11.8+/-4.9%, p=0.022 and 7.4+/-2.6%, p=0.009, respectively) on those sides with relatively preserved baseline task performance. Moreover, the coefficient of variation of tap intervals increased at 5 and 10 Hz compared to 0 Hz (by 70.4+/-35.8%, p=0.038 and 81.5+/-48.2%, p=0.043, respectively). These data suggest that the susceptibility of basal ganglia networks to the effects of excessive synchronization may be elevated across a broad low-frequency band in parkinsonian patients, although the nature of the consequent motor impairment may depend on the precise frequencies at which synchronization occurs.